Multisystem Imaging Manifestations of COVID-19: Viral Pathogenesis and Pulmonary Complications - Shafi Muhammad Khuhawar, Jagdesh Kumar, Khalil Ahmed Sanghro, Bashir Ahmed Chandio, Saleh Muhammad Channa, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To analyze multisystem imaging techniques for diagnosis of Covid-19 viral pathogenesis and pulmonary complications. Study Design: Retrospective study. Place and Duration of Study: Department of Pulmonology, Ghulam Muhammad Mahar Medical College, Sukkur from 1st June 2021 to 31st December 2021. Methodology: Two hundred patients admitted due to Covid-19 positive results were enrolled. Pulmonary consolidations and pneumonia related alterations were observed due to these images. Changes which were related with acute respiratory distress syndrome in complicate Covid-19 cases were also observed. Patients with serious illness were further underwent chest computer topographic imaging scan. Pulmonary-US scan was also performed on the bedside of severe ill Covid-19 patients. In patients with acute respiratory decline and acute dyspnea were also further diagnosed through computed tomography angiography. Results: The mean age of the patients was 41.2±6.5 years. Chest radiograph presented bilateral pneumonia opacities. In a typical progressive pneumonia could be seen through non-contrast enhanced computed tomography imaging in covid-19 patients with glass opacities and bilateral ground glass opacities. In many cases multifocal, patchy as well as distribution findings which were confluent and organizing as pneumonia were also observed. Pulmonary embolism was also identified through computed tomography imaging in Covid-19 patients. Conclusion: Multisystem imaging techniques are significantly important and efficient in diagnosis of various manifestations of Covid-19.